Clinical and dermoscopic features associated with lichen planus‐like keratoses that undergo skin biopsy: A single‐center, observational study. (18th November 2018) - Liopyris, Konstantinos; Navarrete‐Dechent, Cristian; Dusza, Stephen W; Marghoob, Ashfaq A; Deng, Liang; Wilson, Barbara B; Marchetti, Michael A
Abstract: Background/Objectives: Lichen planus‐like keratoses (LPLK) are benign skin lesions that can mimic malignancy; the clinical and dermoscopic features distinguishing lichen planus‐like keratoses from skin tumors have not been extensively studied. The objective of this study was to identify dermoscopic features that may prevent unnecessary biopsies of lichen planus‐like keratoses. Methods: Retrospective, single‐center, observational study of biopsied skin lesions at a tertiary center. We compared 355 lichen planus‐like keratoses to 118 non‐lichen planus‐like keratoses lesions with lichen planus‐like keratosis in the differential diagnosis biopsied from August 1, 2015, to December 31, 2016. The investigators were blinded to the diagnosis of the lesions. Results: Lichen planus‐like keratoses were most frequently non‐pigmented (61.7%), truncal (52.1%), and on sun‐damaged skin (69.6%); the majority occurred in Whites (95.5%) and females (62.8%). Dermoscopically, lichen planus‐like keratoses were more likely than non‐lichen planus‐like keratoses to have scale (42.5% vs 31.4%, P = 0.03) and orange colour (8.2% vs 0.9%, P = 0.01). Among lesions with peppering ( n = 76; 63 lichen planus‐like keratoses and 13 non‐lichen planus‐like keratoses), coarse ± fine peppering (73% vs 38.5%, P = 0.02) and peppering as the only feature (34.9% vs 0%, P = 0.01) were associated with lichen planus‐like keratoses. Conclusions: Lichen planus‐like keratoses can be challenging to distinguish from benign and malignant skin tumors. The presence of dermoscopic scale and orange colour may aid in the recognition of lichen planus‐like keratosis. Coarse peppering and the presence of peppering as the only dermoscopic feature may further aid the identification of pigmented lichen planus‐like keratoses.